Relationship With Exclusive Asking Stunting Events In Children - Asnidar; Safruddin; Emilia Yusram (Jurnal Life Birth, 2019)
Stunting is a linear growth disorder caused by malnutrition in chronic nutritional intake and/or in chronic and recurrent infectious diseases as indicated by high z-core values according to the age of Tb / Ub less than -2 standard deviations. ASI is a safe food for infants to have a balanced composition of nutrients as needed and contains antibodies that can protect babies from the disease so that breastfeeding can guarantee adequate nutrition, prevent pain and death in infants. This study aims to determine the relationship of exclusive breastfeeding with the incidence of stunting in children under five in the working area of the gattareng health center. The research design used is quantitative analytic research with Cross-Sectional Design approach, the sampling technique is consecutive sampling to get respondents as many as 84 respondents from all populations of children under five in the working area of the gattareng health center. Data collection was carried out by distributing questionnaires to respondents and processing data / statistical tests using the Chi-Square Test with a significance value of Î± <0.05. And presented in the form of tables and narration. The results of this study There is a relationship between exclusive breastfeeding and the incidence of stunting with a value of P = 0.001 <0.05. This study concludes that exclusive breastfeeding is in the high category of 49 people (58.3%) and the incidence of stunting as many as 42 people (50.0%).